Writing the Past in Twenty-first-century American Fiction - Lawrie, Alexandra (Edinburgh University Press, 2023)
Writing the Past in Twenty-First-Century American Fiction examines contemporary novels profoundly shaped by a sense of historical consciousness. Authors including Ben Lerner, Colson Whitehead, Dana Spiotta, Hari Kunzru and Garth Greenwell each use flashbacks, historical parallels and non-sequential narrative arrangements to emphasise the re-emergence, in a twenty-first-century context, of historical structures and circumstances. This study explores how these frequent moments of temporal slippage amount to a ‘falling out of time’, as characters are forced to confront the past crises which continue to exert pressure on their own contemporary moment.